2011
DOI: 10.3109/0886022x.2011.618968
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Nephropathology Teaching Modules and User Satisfaction: The Nephrology On-Demand Experience

Abstract: Nephropathology is an integral component of nephrology education. Online teaching sites provide valuable educational materials to learners, but learner satisfaction has not been measured. We developed a nephropathology website and measured learners' satisfaction. The Nephrology On-Demand Histopathology website (http://blog.ecu.edu/sites/ nephrologyondemand/?page_id=4502) provided nephropathologic specimens with explanations. Users were asked to complete a Likert-based survey (1-strongly agree . . . 5-strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The use of current web-based learning tools such as blogs, wikis, podcasts, and other social media must be strongly considered during fellowship training (32)(33)(34)(35)(36)(37). These teaching tools may not only increase interest in nephrology, but may also enhance and maintain interest during nephrology fellowship.…”
Section: What Can Be Done To Promote Interest In Nephrology and Careementioning
confidence: 99%
“…The use of current web-based learning tools such as blogs, wikis, podcasts, and other social media must be strongly considered during fellowship training (32)(33)(34)(35)(36)(37). These teaching tools may not only increase interest in nephrology, but may also enhance and maintain interest during nephrology fellowship.…”
Section: What Can Be Done To Promote Interest In Nephrology and Careementioning
confidence: 99%
“…In another study, with oral prednisolone 1 mg/kg/day, kidney outcomes were improved in patients with CES 94. In contrast, several studies have shown that corticosteroids are not effective, especially in the long term 97…”
Section: Treatment and Managementmentioning
confidence: 92%
“…Web-based nephropathology teaching modules have also been well received with increased learner satisfaction. 12 Although online or Web-based learning ( Table 3 ) could enhance the knowledge and satisfaction of all fellows, this tool could certainly play an important role in the nephropathology education of fellows in programs that do not have a robust on-site nephropathology staff and services. For example, a recently initiated, Web-based nephropathology educational conference known as “GlomCon” discusses difficult glomerular disease cases among trainees, nephrologists and nephropathologists from community medical centers and academic institutions.…”
Section: Methodsmentioning
confidence: 99%